2018
DOI: 10.1002/ejoc.201800298
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in [Cp*MIII] (M = Co, Rh, Ir)‐Catalyzed Intramolecular Annulation Through C–H Activation

Abstract: This review aims to summarize the recent advances in the field of Cp*MIII (Co, Rh, Ir)‐catalyzed C–H activation followed by subsequent intramolecular reaction. This approach has allowed the synthesis of valuable heterocycles with high structural diversity and complexity, including polycyclic and macrocyclic compounds. In this review, a particular attention has been made to the nature of the coupling partner (alkene, alkyne, etc) and its connection either to the aryl (or vinyl) group or to the directing group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(26 citation statements)
references
References 88 publications
1
25
0
Order By: Relevance
“…These two methods can be also extended to pyrrole derivatives to access fused 5-azaindoles. The above works illustrated the application of C-H activation and intramolecular annulation (Peneau et al, 2018) to construct the pyridine ring with concurrent formation of a fused ring by using in situformed alkyne-tethered substrates.…”
Section: Construction Of Polycyclic Heterocycles Fused Pyridines and mentioning
confidence: 99%
“…These two methods can be also extended to pyrrole derivatives to access fused 5-azaindoles. The above works illustrated the application of C-H activation and intramolecular annulation (Peneau et al, 2018) to construct the pyridine ring with concurrent formation of a fused ring by using in situformed alkyne-tethered substrates.…”
Section: Construction Of Polycyclic Heterocycles Fused Pyridines and mentioning
confidence: 99%
“…Therefore, with the aim of overcoming those issues, the use of more earth-abundant first-row transition metals (nickel, iron, manganese, copper, and cobalt, for instance) has started to gain importance. 6 Among them, cobalt catalysts bearing pentamethylcyclopentadienyl ligands (Cp*) have recently started to gain center stage, 7 after the publication of Matsunaga and Kanai’s pioneering work, reported in 2013, on the utilization of high-valent Cp*Co(III). They demonstrated that a nucleophilic Co(III) organometallic species was generated via C–H activation, exemplified by the conjugate addition of 2-phenylpyridine 1 to unsaturated ketones 2 ( Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since some reviews on this field have recently been published, 7 herein, we will present our perspective on the state of the art of this emerging area of catalysis. In this perspective article, we will focus on the development and the latest advances of Cp*Co(III)-catalyzed C–H hydroarylation of alkynes and alkenes.…”
Section: Introductionmentioning
confidence: 99%
“…Rhodium-catalyzed C-H activation/cyclization has recently been pursued for constructing diverse heterocyclic systems [ 17 , 18 , 19 , 20 ]. Within rhodium catalysis, amide has attracted attention because of their particularly stable functionality.…”
Section: Introductionmentioning
confidence: 99%